Study the Relation between Banking System Concentration and Unemployment-Rate in Iran - Dorraji, Ayoob; Abbasi, Gholamreza (International Journal of Economics and Financial Issues, 2017)
In this study, we investigated the relation between banking system concentration and unemployment-rate in Iran. Research aims included identifying effect of internal factors of banks on employment and also recognition of effect of bank internal factors on unemployment rate. In this study, dependent variable is unemployment rate (UIR) and independent variables are: bank concentration (BC), total size of bank (BS), credit risk (CR), liquidity risk (LR), and inflation control variable (ICV). Statistical population includes all banks of Iran. In order to study co-integration of variables, auto regression distributed lag method was used. And then research variables were investigated with taking hydro statistic and structural break into account. And they are tested by hydro statistic test. Some of them were in static level. And some of them became static by differentiation. In investigation of research hypothesis, short term, and long term relations for research models were met. Results indicated that banking concentration and unemployment have negative relation. In other word, by increase of banking concentration, and by increase of bank size, unemployment rate is decreased. Internal factors of banks have negative relation with unemployment rate while with increase of size sector bank, unemployment rate is decreased. Credit rate has positive relation so with increase of credit rate, unemployment rate is increased. Liquidity rate have negative relation with unemployment so with increase of credit rate, unemployment rate is increased. Liquidity rate has negative relation with unemployment so by increase of Liquidity rate, unemployment rate is increased so relation of inflation variable with unemployment rate is positive. Keywords: unemployment rate, banking concentration, credit rate, Liquidity rate, inflation JEL Classifications: E5, E31, J64